CO2 EOR with in-situ CO2 capture, a Neuquina basin oxycombustion case study - Gallo, Gonzalo; Puliti, Raul; Torres, Rodolfo; Eleonora Erdmann (CT&F - Ciencia, Tecnología y Futuro, 2020)
Given the growing interest in the capture and utilization of CO2 in recent years, several technologies have emerged that seek to generate CO2 in-situ at a low cost. There are promising developments, which allow capturing CO2 with sufficient purity to be used for EOR. Oxycombustion has high potential in the region as this technology benefits from gas production with a high CO2 content, which significantly reduces the cost of capture. Additionally, carbon dioxide separation techniques such as air capture, fuel cells, amines, and membranes are considered. Argentina has several fields, which produce gas with high CO2 content benefiting Oxycombustion economics. The paradigm change not only occurs in technology but also in the implementation schemes. The vast majority of the development of CO2 EOR are carried out in the USA with very low CO2 costs and high availability. When considering the costs of CO2 per ton (metric ton) that could be obtained in Argentina, and financial variables such as high discount rates, it is clear that the injection model has to be optimized for these conditions. In order to optimize profitability, it is crucial to improve the payout time and the usage of CO2. In one hand, smaller slugs lead to better CO2 utilization rates (oil produced/CO2 injected) while larger slugs lead to faster oil production response. We observed that due to the high discount rates in the area, faster production response has a higher economic impact that sweep efficiency or breakthrough times. It seems to be better to sacrifice overall recovery factor in order to extract oil as soon as possible. Optimal injection schemes where found for different scenarios. Additionally, starting the project early is a key parameter for both technical and economic success. Another key technical difference is that the available CO2 volume for injection is constant due to the nature of these capture techniques. Unlike purchasing CO2 from a pipeline, where gas can be purchased as needed, Oxycombustion (or other capture methods) produces a continuous stream limiting injection flexibility. All produced CO2 must be injected as it is being produced and, until production gas reaches a CO2 content high enough to assure MMP, CO2 injection stream cannot exceed the maximum CO2 capture capacity. CO2 EOR has significant advantages over Chemical EOR due to its significant recovery factors and early response. Additionally, this technology applies to reservoirs of low permeability and / or high temperature where the polymer can have problems of injectivity or degradation.